GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR - Masniar, Masniar; Tobari, Tobari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The principal's leadership style is a pattern of consistent behavior that is shown by the leader and known to other parties when the leader tries to influence the activities of others. The research objective was to determine the leadership style of the principal, including; (1) discipline; (2) commitment; (3) ability and (4) teacher responsibility. Qualitative approach with descriptive method, data collection techniques carried out by interview guidelines, observation guidelines, and documentation studies. Subjects of the study were principals, teachers and supervisors at Elementary School 25 Pulau Rimau. The results of the study were found; (1) the principal's leadership style in improving teacher discipline, is the style of telling (telling), in addition to style telling, the principal also applies a situational style; (2) the principal's leadership style in increasing teacher commitment is the style of selling (consultative) by directing the teacher to complete the task; (3) the principal's leadership style in enhancing the ability of the teacher, namely the participatory style that is applied during the internal meeting of the teacher council and other meetings; and (4) the principal's leadership style in increasing teacher responsibility, is a delegative style, namely sharing authority with members to carry out organizational tasks. It is hoped that supervisors and principals can provide encouragement and direction in work on discipline, commitment, ability and responsibility of teachers effectively and efficiently to improve work in schools.